Novel approach to automated fingerprint recognition - Abdul Rahman, Abdul Wahab; S., H.Chin; E., C.Tan (IET Digital Library, 1998)
The paper describes an enhanced fingerprint recognition system consisting of image preprocessing, feature extraction and matching that runs accurately and effectively on a personal computer platform. The image preprocessing includes histogram equalisation, modification of directional codes, dynamic thresholding and ridgeline thinning which are sufficient to enhance the image to a state ready for feature extraction. Only features extracted are stored in a file for fingerprint matching. The matching algorithm presented is a modification and improvement of the structural approach. Experimental results acquired for matching are accurate, reliable and fast for implementation using a PC and a fingerprint scanner. The proposed fingerprint recognition scheme can provide an efficient way of automated identification and can be extended to numerous other security or administration applications.